ANALISIS PENGARUH DESAIN PRODUK, KUALITAS PRODUK, HARGA KOMPETITIF DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen Distro N19AB Karangploso Malang) - Mq Agung; N Rachma; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to determine the effect of product design, product quality, competitive price and brand image on purchasing decisions of consumer case studies N19AB Karangploso Distro Malang. This research was carried out to consumers of the N19AB Distro, and the population in this research was all consumers who had made a purchase at Distro N19AB Karangploso Malang. Samples were taken by questionnaire method. Sample size is 75 people. The data analysis technique used is multiple linear regression. The results showed that: 1). Product design has a significant effect on consumer purchasing decisions at N19AB Karangploso Malang distro. 2). Product quality has a significant effect on consumer purchasing decisions at N19AB Karangploso Malang distro. 3). Competitive prices have a significant effect on consumer purchasing decisions at N19AB Karangploso Malang distro. 4). Brand image has a significant effect on consumer purchasing decisions of N19AB Karangploso Malang distro. 5). Product design, product quality, competitive price and brand image have a simultaneous effect on consumer purchasing decisions N19AB Karangploso distro Malang.Keywords: product design, product quality, competitive price, brand image, purchasing decision